Co-precipitation method for preparation of Bi3TiNbO9 powders - Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Patil, S. D.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure, ultrafine, single phase Bi3TiNbO9 (BTN). An aqueous ammonium hydroxide solution was used to simultaneously precipitate Bi3+, Ti4+ and Nb5+, cations as hydroxides under basic conditions (pH similar to 9). No pyrochlore phase was found while heating powder at 500 degrees C and pure BTN phase was found to be formed by X-ray diffraction (XRD). For comparison, BTN samples were also synthesized by the traditional solid state method. The sequence of phase formation in both cases were investigated by XRD studies. (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; Oxides; XRD

Synthesis of bismuth titanate (Bi4Ti3O12)powders via calcination of microwave-hydrothermally (MH) derived precursor - Khollam, Y. B.; Deshpande, S. B.; Samuel, V.; Potdar, H. S. (Indian Journal of Engineering and Materials Sciences, 2008)
Micrometer sized platelet-like particles of bismuth titanate (Bi4Ti3O12) ire prepared successfully by the calcination of a mixed-precursor in air. The mixed precursor is precipitated Under microwave-hydrothermal (MH) treatment via dissolution-recrystallization kinetics. The mixed precursor is precipitated in-situ by giving MH treatment (at 200 degrees C, 200 psi, and 30 min hold time) to the hydrolysed slurry containing Bi and Ti cations. The slurry was prepared by adding 20% aqueous KOH precipitant solution to a well-mixed stoichiometric nitrate solution containing Bi and Ti cations. XRD results revealed that the as-dried precursor consisted of a homogenous mixture of non-crystalline particles of Bi2O3 and TiO2. The calcination of the as-dried precursor at 700 degrees C/2 h in air resulted ill the formation of micron sized platelet like single-phase Bi4Ti3O12 powders having orthorhombic structure.
Keywords: Bi4Ti3O12; MH processing; SEM; XRD